Penggunaan Model Pembelajaran Project Based Learning dan Critical Thinking pada Mata Pelajaran Pendidikan Agama Islam untuk Meningkatkan Kompetensi Profesional Guru Sekolah Dasar di Kecamatan Ciampea - Lahudin; Ami Primarni; Riyanto (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This study aims to examine the understanding and implementation of Project-Based Learning (PjBL) in Islamic Religious Education (PAI) instruction in 24 elementary schools in Kecamatan Ciampea. The results show significant variations in PAI teachers' understanding and application of PjBL. Fifty percent of the teachers have successfully implemented PjBL consistently, thanks to strong support from school principals and adequate educational resources. These teachers have been able to design effective PjBL-based learning projects, allowing students to actively engage in learning and develop critical thinking and creativity. However, 30% of the teachers faced challenges in optimal implementation, particularly due to time constraints and insufficient resources. These teachers require further skill development to better integrate PjBL into daily learning processes. Meanwhile, 20% of the teachers demonstrated a minimal understanding of PjBL and require additional training. These findings highlight the importance of ongoing training, as well as institutional support and resource access, to enhance the effective application of PjBL. The study recommends that schools in Kecamatan Ciampea strengthen teacher training and provide more adequate resources to support the implementation of PjBL, aiming to improve the relevance and meaning of PAI learning.